Intra-abdominal pressure and residual renal function decline in peritoneal dialysis: a threshold-based investigation - Jingjing Zhang; Lei Song; Zhongwei Ma; Lina Sun; Xiaoqing Wang; Duanyan Liu; Feng Huang; Yulin Man (Renal Failure)
Background The potential impact of elevated intra-abdominal pressure (IAP) on residual renal function (RRF) has not been determined. The objective of this study was to investigate the relationship between IAP and the rate of RRF decline in newly initiated peritoneal dialysis (PD) patients, and to identify the optimal IAP threshold value for delaying the deterioration of RRF.Methods A cohort of 62 newly initiated PD patients who completed both 6- and 12-month follow-up evaluations was obtained using the Durand method. A logistic regression model was used to identify variables associated with a rapid decline in RRF. Receiver operating characteristic (ROC) curves were generated to determine the optimal threshold value. Another retrospective cohort analysis was performed to validate the identified critical value.Results For each 1 cmH2O increase in IAP, the risk of a rapid decline in the RRF increased by a factor of 1.679. Subsequent analysis revealed that patients in the high IAP group had more significant decreases in residual renal estimated glomerular filtration rate (eGFR) (Z = −3.694, p < 0.001) and urine volume (Z = −3.121, p < 0.001) than did those in the non-high IAP group. Furthermore, an IAP ≥15.65 cmH2O was a robust discriminator for the prediction of the rate of RRF decline.Conclusion Patients in the high IAP group experienced a more rapid decline in RRF. Additionally, an optimal critical pressure of 15.65 cmH2O was identified for predicting the rate of RRF decline. IAP, as one of the factors contributing to the rapid decline in RRF in the first year of PD, should be given due attention.